Using questions to think : how to develop skills in critical understanding and reasoning - Dickman, Nathan Eric (London, England : Zed Books, 2021)
"Our ability to think, argue and reason is determined by our ability to question. Questions are a vital component of critical thinking, yet we underestimate the role they play. Using Questions to Think puts questioning back in the spotlight. Naming the parts of questions at the same time as we name parts of thought, this one-of-a-kind introduction allows us to see how questions relate to the definitions of propositions, premises, conclusions, and the validity of arguments. Why is this important? Making the role of questions visible in thinking reasoning and dialogue, allows us to: - Ask better questions - Improve our capability to understand an argument - Exercise vigilance in the act of questioning - Make explicit what you already know implicitly - Engage with ideas that contradict our own - See ideas in broader context Breathing new life into our current approach to critical thinking, this practical, much-needed textbook moves us away from the traditional focus on formal argument and fallacy identification, combines the Kantian critique of reason with Hans-Georg Gadamer's hermeneutics and reminds us why thinking can only be understood as an answer to a question"--
Preface Introduction: An Age of Answers Part I: Make Questions Explicit for Thinking 1. -- Thinking Only Happens in Complete Thoughts 2. -- What Do Questions Do to Complete Thoughts? 3. -- A Logic of Question-and-Answer Part II: Make Questions Explicit for Reasoning 4. -- Reasoning Only Happens in Explicit Arguments 5. -- What Do Questions Do to Arguments? 6. -- A Rationality of Questioning-and-Reasoning Part III: Make Questions Explicit in Dialogue 7. -- Dialogue Only Happens in Constructive Reconciliations 8. -- What Do Questions Do to Dialogues? 9. -- A Dialectic of Questionability-and-Responsibility Conclusion: The End(s) of Questions Appendix for Instructors Glossary Bibliography Index
Includes bibliographical references (pages [233]-244) and index.
Also published in print.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Mode of access: World Wide Web.
Keywords: Thought and thinking; Critical thinking; Reasoning; Questioning; Philosophy: logic; Electronic books